GROWTH TRAIT’S AND YIELD EVAIUATION OF ITALIAN MAIZE INBRED LINES BY FULL DIALLEL CROSS - & et al., Abed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
To evaluate five maize inbred lines imported from Italy by daillel and reciprocal crosses which predict from its, by estimate the heterosis ,general and specific combining ability effect(Gca,Sca,Rca), type of gene action and degree of dominance for growth traits and total yield. Field experiment was conducted during the two successive seasons of 2013 , during spring seasons full –diallel cross was carried out among inbred lines, In fall season a comparison experiment between the parents and the hybrids was carried by using randomized complete block design. The result show significant differences for the plant height (PH)(cm), ear height (EH)(cm) ,number of leafs per plant(NLP) ,leaf area index(LA) ,the biomass(BI) and total yield per area(TY)(tan.h-1) which refer to high variation among the parents. The inbred line Agostano excel in TY (tan .h-1), NLP and the BI, as such the DSP177 was excellence in ether traits and the cross between parents was deign high TY reach to 7.88 tan.h-1.The results of heterosis revealed the 20 cross in PH,15 cross in EH,14 cross in NLP and LAI, 17 cross in BI and 15 cross in TY a positive direction desired for heterosis , best values for it given from the hybrid Hi39Antiguao x FLO1240 (128.9%) in TY . The genetic analyses emerged the greatest role of inheritable traits which to demonic effect and some for this inheritable to additive effect where notes high significant for the GCA,SCA and RCA but the rate of the Gca / Sca more loss than one for all traits as well as the rate of Gca / Rca except LAI in reciprocal cross which it more than one , as such the dominance genetic variance(δ2D) which higher than the additive genetic variance(δ2A), and high bored sense heritability (h2bs%) ,and lower narrow sense heritability (h2ns %)for the daillel cross all traits as well as the degree of dominance which more than one except the LA in reciprocal cross , It can be conclude the possibility of benefit to breed the parents to produce diallel cross by using the hybridization method is the hybridization and the hybridization followed by selection to produce reciprocal cross .